Endoscopic Drainage of Pseudocysts - Song, Tae Jun (The Korean Society of Gastrointestinal Endoscopy, 2014)
During the last decade, great progress has been made in minimally invasive endoscopic techniques. For pancreatic pseudocysts (PPCs), endoscopic drainage has become the first-line therapeutic option. Recent advances in therapeutic endoscopic ultrasound (EUS)-related techniques have focused on EUS-guided transmural drainage, which is now replacing the conventional endoscopy-guided transmural drainage. While transmural drainage is usually performed using multiple plastic stents with or without a nasocystic drain, fully covered self-expandable metal stents are now being used with increasing frequency. In this review, we discuss some of the controversies related to the endoscopic drainage of PPCs.